Diagnóstico do sistema ambiental da bacia hidrográfica do Alto Viamão, Mato Verde - MG - Oliveira, Rachel Inez Castro de (2007)
This paper presents a dissertation, on the diagnosis of the environmental system of the high Viamão hydrographic basin, located in Mato Verde city, Minas Gerais, the dissertation aimed to detect the main features and problems of this basin. A bibliographic research was carried out the researched subjects were system theory, hydrographic basin and the use of techniques of remote sensing and geoprocessing as useful tools for finding out the high Viamão basin diagnosis. Initially, all the environmental system components were studied aiming to understand the structure and function of each one of them. After that, there was an integration of the components according to each problem identified in the basin. The research area recognition was possible through topographical maps, geological maps, exploratory maps of Minas Gerais North side, satellite images and working in the field of the research which was essential for the hydrographic basin diagnosis, including MatoVerde city, and mainly, high Viamão hydrographic basin area. Then, it was possible to detect the main environmental problems in this area. The study revealed that this area presents low agricultural potentiality, according to the evaluation results for agricultural aptitude. And according to the way the soil is used and occupied, it was possible to notice that in almost all the area, the soil is used inappropriately. Besides this, several social and economic problems could be identified in the same area, for instance, the population low quality of life and the lack of a tourism planning. In order to contribute to ease the diagnostic problems, there are some suggestions to complement this dissertation.